(3GddBdj aj TQM CeGdj GdbGdjs - (3CHhYHjO YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSjs; (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s
(3ChdgG (B:s
(3TQMJ ajg ajg ef GdfhGOQ GdJj CHhYdi ESeGYjd Hf GdbGSe GdbGdj eG CZad s
(3BNQgG (B:s
(3hPcQ CHhYdj bhdge(B: (3CVQg ef YjT LRi s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B161 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs